Spontaneous quantity discrimination in a family-living lizard. (28th April 2021) - Szabo, Birgit; Noble, Daniel W A; McCloghry, Kaitlin J; Monteiro, Marco E S; Whiting, Martin J
Abstract: While foraging or during social interactions, animals may benefit from judging relative quantity. Individuals may select larger prey or a patch with more food and, likewise, it may pay to track the number and type of individuals and social interactions. We tested for spontaneous quantity discrimination in the gidgee skink ( Egernia stokesii ), a family-living lizard. Lizards were presented with food quantities differing in number or size and were able to select the larger quantity of food items when they differed in number but not when items differed in size. We show, for the first time, superior spontaneous discrimination of items differing in number over size in a lizard species, which contrasts with previous findings. Our simple method, however, did not include controls for the use of continuous quantities, and further tests are required to determine the role of such information during quantity discrimination. Our results provide support for the use of the parallel individuation system for the discrimination of small quantities (four or fewer items). Lizards might, however, still use the approximate number system if items in larger quantities (more than four) are presented. Overall, we uncovered evidence that species might possess specific cognitive abilities potentially adapted to their niche with respect to quantity information (discrete and/or continuous) and the processing system used when judging quantities. Importantly, our results highlight the need for testing multiple species using similar testing procedures to gain a better understanding of the underlying causes leading to differences across species. Abstract : The ability to spontaneously discriminate quantities is widespread across animals. If it is a basic ability shared by all or if it has emerged specifically to deal with numerical problems is unclear. Reptiles can spontaneously pick the larger of two food quantities usually performing better when differing in size but gidgee skinks, a social lizard species, performed better when quantities differed in number. Gidgee skinks might require a number sense to deal with social challenges.